Bone regenerative properties of injectable PGLA-CaP composite with TGF-beta1 in a rat augmentation model. - Plachokova, A. (2007)
The aim of this study was to examine the bone augmentation properties of an injectable composite consisting of PLGA microspheres/CaP cement (20/80), and the additional effect of loading PLGA microspheres with TGF-β1 (200 ng). For this purpose, PLGA/CaP composites (control) and PLGA/CaP composites loaded with TGF-β1 (test group) were injected on top of the skulls of 24 Wistar rats. Each rat received 2 materials from the same experimental group, and in total 48 implants were placed (n = 8). After 2, 4, and 8 weeks the results were evaluated histologically and histomorphometrically. The contact length between the implants and newly formed bone increased in time, and was significantly higher for the TGF-β1-loaded composites after 2 weeks. Also, bone formation was significantly higher for the TGF-β1-loaded composites (18.5% ± 3) compared to controls (7.21% ± 5) after 8 weeks of implantation. Immunohistochemical staining demonstrated massive inflammatory infiltrates in both groups, particularly at 2 weeks, which decreased substantially at 4 and 8 weeks. In conclusion, injectable PLGA/CaP composites stimulated bone augmentation in a rat model. The addition of TGF-β1 to the composite significantly increased bone contact at 2 weeks and enhanced new bone formation at 8 weeks.